Integration and disintegration of EMU government bond markets - Christian Leschinski; Michelle Voges; Philipp Sibbertsen (Econometrics, 2021)
It is commonly found that the markets for long-term government bonds of Economic and Monetary Union (EMU) countries were integrated prior to the EMU debt crisis. Contrasting this, we show, based on the interrelation between market integration and fractional cointegration, that there were periods of integration and disintegration that coincide with bull and bear market periods in the stock market. An econometric argument about the spectral behavior of long-memory time series leads to the conclusion that there is a stronger differentiation between bonds with different default risks. This implied the possibility of macroeconomic and fiscal divergence between the EMU countries before the crisis periods.
Keywords: C32; C14; C58; E43; 330; EMU; fractional cointegration; market integration; yield spreads